1968
DOI: 10.1002/pssb.19680300218
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Velocity and Attenuation in Alkali Halides Containing CN I. Experimental Results

Abstract: The ultrasonic velocity and attenuation were measured in KCl, KBr, KI, and NaCl containing CN-as a function of acoustic mode, temperature, concentration, frequency, plastic deformation, and static bias stress. The results are not compatible with stress ordering of an elastic dipole tensor represented by an ellipsoid of rotation with CN-axes having Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For various defects it is possible t o align the elastic dipoles by uniaxial stress almost completely a t low temperature. This alignment has been monitored by different methods, for example by measurements of the dichroism of the UV-or IR-bands [l to 41 or by ultrasonic methods [5]. Successful candidates in the search of paraelastic centres have been off-centre defects [ S ] and small molecular ions like OH-, CN-, and NHF [l to 41, since these centres provide sufficient reorientations1 rates at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For various defects it is possible t o align the elastic dipoles by uniaxial stress almost completely a t low temperature. This alignment has been monitored by different methods, for example by measurements of the dichroism of the UV-or IR-bands [l to 41 or by ultrasonic methods [5]. Successful candidates in the search of paraelastic centres have been off-centre defects [ S ] and small molecular ions like OH-, CN-, and NHF [l to 41, since these centres provide sufficient reorientations1 rates at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the multiexponential decay with the two rates 1 and 2 gives rise to quite an intricate relaxation spectrum; thus an experimental investigation of the frequency dependence would seem most promising. Simliar behaviour was also found for an E g -mode [9] contradicting the simplest model of an [111]-defect. Even asymmetries cannot explain this feature in a simple way.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 82%
“…Early measurements in KCl:CN samples [9] in the classical regime (k B T ) showed that the change of sound velocity of a T 2g -mode (ê = [110],k = [001]) varies as expected similiar to 1/T with temperature. Yet in addition, these experiments showed a change of sound velocity for an E g -mode (ê = [110],k = [110]) with an amplitude of about ten times smaller than the T 2g ones, whereas this mode should be unaffected according to the simplest model of a symmetric [111]-tunnelling defect.…”
Section: Introductionmentioning
confidence: 95%
“…Early measurements in KCl:CN samples [9] in the classical regime (k B T ) showed that the change of sound velocity of a T 2g -mode ( ê = [110], k = [001]) varies as expected similiar to 1/T with temperature. Yet in addition, these experiments showed a change of sound velocity for an E g -mode ( ê = [110], k = [1 10]) with an amplitude of about ten times smaller than the T 2g ones, whereas this mode should be unaffected according to the simplest model of a symmetric [111]-tunnelling defect.…”
Section: T 1u T 2gmentioning
confidence: 95%